Defining contralateral adrenal suppression in primary aldosteronism: implications for diagnosis and outcome. (6th January 2015) - Kline, G.A.; Chin, A.; So, B.; Harvey, A.; Pasieka, J.L.
Summary Objective Unilateral primary aldosteronism (PA) should have a contralaterally normal and therefore suppressed adrenal zona glomerulosa. However, there is no validated definition of adrenal suppression. We created two biochemical hypotheses of adrenal suppression based upon measurements taken during adrenal vein sampling (AVS) to determine whether either proved useful for interpretation of AVS or prediction of hypertension outcome in operated cases. Design Retrospective database analysis. Patients Ninety‐nine cases of PA from a tertiary hypertension unit. Measurements Hypothesis 1 was the proportional suppression of the uninvolved/lowest adrenalaldo/cortisol to IVCaldo/cortisol ratio pre‐ and post cosyntropin. Hypothesis 2 was the absolute decrease in the uninvolved adrenalaldo/cortisol ratio after cortrosyn injection. ROC analysis performed using lateralization and hypertension resolution as the outcomes of interest. Results Hypothesis 1 proved highly predictive of lateralization with a ROC AUC of 0·958, P < 0·0001, giving adrenalaldo/cortisol:IVCaldo/cortisol <1·4 as the optimized criterion (sensitivity 90%, specificity 94%). For blood pressure outcomes in the surgical subgroup (n = 52), hypertension resolution was most commonly seen among subjects with adrenal suppression by both definitions although there was significant overlap with subjects requiring ongoing medication. Conclusions Post cosyntropin suppression of the uninvolved adrenal‐to‐IVC ratio is a highly useful definition of adrenal suppression that accurately predicts unilateral PA. This may be particularly useful in a case where AVS fails to catheterize one of the adrenal veins but suppression is seen on the other side. Adrenal suppression may also predict blood pressure outcome, however, a much larger PA database is likely necessary to determine the relative contribution of this predictor.